Harm reduction and animal welfare in the use of pet facilitated therapy (PFT) from one health perspective - Zaw, Cho Cho; Ahmad, Norfadzilah; Myat Min, Myat Min (Scholars Journal of Applied Medical Sciences, 2019)
“One Health” approach includes policies and programmes which aims to improve public health and consider the overall welfare of animal, human and environment. Pet facilitated therapy (PFT) comprises the use of animals as part of complementary and alternative therapy. Thus, the concept of “One Health” should be reflected in PFT in order to achieve the wellbeing of humans, animals, and environment. While the use of animals for human wellbeing, the risks involved from the animal and their welfare should be considered. Thus, this paper aims to explore the harm reductions, and animal welfare in the use of PFT from one health approach. Analytical literature review was used as a methodology for this study and the findings are categorized into four themes such as (i) the types of animal used in PFT, (ii) the potential benefits of PFT for human wellbeing (iii) environmental concern and harm reduction, and (iv) animal welfare in PFT. It is observed that dogs are used as the majority pet in PFT, and other different species such as cat, dolphin, horse, donkey, farm animals, bird, exotic and aquatic animals are also used. The potential benefits of PFT have been highlighted in people with disabilities, physical, mental and neurological disorders, elderly with dementia and Alzheimer, and children with special needs, and juvenile adolescents. Under environmental concern and risk reduction in PFT, the possible zoonoses are identified and presented. Animal welfare is considered to have mutual benefits for both parties involved in PFT. This paper serves as a source of public awareness on PFT and recommended to use it in the area of pediatric, palliative, juvenile and geriatric care in addition to conventional treatment after carefully removing or reducing its limitations